OPTIMIZATION OF IBA AND ACTIVATED CHARCOAL ON IN VITRO ROOTING OF KOPYOR COCONUT - Amanda Putri Viony; Susiyanti; Sulastri Isminingsih; Zahratul Millah; Kartina AM (Gunung Djati Conference Series, 2026)
Kopyor coconut (Cocos nucifera L.) is a high-value commodity, but its conventional propagation is constrained by abnormal endosperm, resulting in poor germination. In vitro embryo culture on Y3 medium offers an alternative to improve propagation efficiency. This study evaluated the effects of Indole-3-Butyric Acid (IBA) and activated charcoal on in vitro growth of kopyor coconut embryos cultured on Y3 medium. The experiment used a factorial Randomized Block Design (RBD) with two factors, IBA concentrations (0, 1, 2, and 3 mg L⁻¹) and activated charcoal (0, 1, and 2 g L⁻¹), with four replications. Observed parameters included time to root emergence, explant height, and survival percentage. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Results showed that activated charcoal significantly affected time to root emergence and explant height, while IBA and its interaction with activated charcoal were not significant for all parameters. The application of 1 g L⁻¹ activated charcoal produced the fastest root emergence at 9.25 weeks after culture and achieved 100% explant survival. In conclusion, activated charcoal at 1 g L⁻¹ effectively enhances early in vitro development of kopyor coconut embryos by accelerating root emergence and improving survival, while IBA up to 3 mg L⁻¹ does not significantly affect early growth responses.